Implementasi Kurikulum Merdeka Belajar dalam Pengembangan Kemampuan Berpikir Kritis pada Pembelajaran Pendidikan Agama Islam - Syifaun Nadhiroh; Isa Anshori (Fitrah: Journal of Islamic Education, 2023)
This study aims to analyze the implementation of the independent curriculum in developing critical thinking skills in learning Islamic Religious Education at SMP Muhammadiyah 1 Sidoarjo. Using qualitative research methods, the type of data collected is in the form of qualitative and quantitative. Data collection techniques using observation, interviews and documentation, primary and secondary sources. The data collected was analyzed through the process of data reduction, data display and drawing conclusions, while to check the validity of the data triangulation was carried out with sources and a team of experts. The results of the study show that: 1) The application of the independent curriculum in the learning process of Islamic Religious Education focuses on the activeness of students in the hope that their critical thinking skills will develop; 2) Implementation of the independent learning curriculum in Islamic Religious Education Learning contributes to the development of students' critical thinking skills. 3) Improving the ability to think critically in learning out by teachers using various approaches, strategies, methods, learning techniques, and applying innovative learning media. Teachers train students to think critically by reasoning, assessing and making a decision to determine the advantages and disadvantages that must be faced systematically.